Aplikasi Pita Kupu-Kupu pada Busana Exotic Dramatic Style - Dina Gusmita; Mega Kencana; Desi Trisnawati; Fendi Nofrian (INDO PUBLISHING, 2026)
The creation of this fashion collection was inspired by the artist's fascination with the butterfly bow a decorative element that offers aesthetic value and enhances the garment's design character. Beyond mere ornamentation, the bow shapes the silhouette, directs visual focus, and lends a feminine, artistic quality to the attire. The work embodies an